Balance and agility in mountain bikers: a reliability and validity study on skills affecting control in mountain biking - Buchholtz, Kim Anne (Department of Human Biology, 2022)
Background Cycling is a popular recreational and competitive form of physical activity and method of transport. Cycling is broadly categorised as road cycling or mountain biking, and each form presents unique challenges and has different skill requirements. While cycling, in general, provides many benefits to both physical health and social behaviours, there are legitimate concerns about injuries related to both road and mountain cycling. Most of the available research presents the injury incidence in commuter or road cycling, with an apparent lack of evidence in mountain biking. The van Mechelen model of injury prevention outlines four stages in injury prevention research; the first stage investigates the extent of the injury and provides the basis on which the remaining stages depend. Based on the van Mechelen conceptual model, the broad aim of this thesis was to investigate acute injury epidemiology in mountain biking and the factors affecting bicycle control and falling. Investigations We performed a systematic review of the incidence of injury in mountain biking. Acute injury incidence ranged from 4% to 71% in cross-country mountain bike races. The causal indicators of bicycle control may include balance, agility and visual perception. In a pilot study, we developed novel tests to assess static bicycle balance and bicycle agility as measures of bicycle control. In the following study, we developed additional dynamic bicycle balance with four increasingly difficult levels. In this study, twenty-nine participants attended three days of repeated testing for reliability assessments of these tests. Participants also completed an outdoor downhill run. Performance in the balance tests were compared to performance in the outdoor downhill test to assess their ecological validity. All tests were assessed for reliability using typical error of measurement, standardised typical error, intraclass correlation coefficients, limits of agreement, effect sizes and repeated measures ANOVA's (with post hoc testing) analyses. The novel bicycle balance and agility were significantly associated with the performance in the outdoor downhill run (r=-0.51 to 0.78; p=0.01 to 0.0001). Cognitive and physical fatigue are factors that may contribute to loss of control of the bicycle. In our final study, we aimed to assess the effect of these factors on the performance in the novel tests. Rate of perceived exertion was significantly increased for all tests following physical fatigue (Cliff's d effect size= 0.27-0.40; p=0.001 to 0.037), but balance and agility performance were not affected. Cognitive fatigue had no effect on balance and agility performance. The fatigue induced in these protocols was insufficient to change performance in the bicycle-specific balance and agility tests. This indicates that either the fatigue protocols did not sufficiently replicate the fatigue experienced in mountain biking or that the tests are too blunt to be affected by the magnitude of fatigue in these protocols. Conclusion The overall incidence of injury in mountain biking is difficult to determine due to different injury definitions in the research. However, the available data clearly indicates an area of concern in sports and exercise medicine. We developed novel tests to assess the skill components of balance and agility on a mountain bike. The novel bicycle-specific tests are robust assessments of mountain biking performance and can be applied in clinical and research environments to determine bicycle control. Cognitive and physical fatigue did not affect performance on these novel tests. Based on the overall findings of our studies, we recommend that further research is conducted on the epidemiology of mountain biking injuries. The effect of fatigue on the novel tests needs to be investigated further using a combination of physical and cognitive fatigue.